Enantioselective resolution of γ-lactam utilizing a novel (+)-γ-lactamase from Bacillus thuringiensis. (September 2018) - Su, Yu; Gao, Shuaihua; Li, Hongxia; Zheng, Guojun
Graphical abstract: Highlights: A novel (+)-γ-lactamase was discovered from Bacillus thuringiensis by gene mining method. The (+)-γ-lactamase could catalyze the bioresolution of γ-lactam with a high ee of 99.8% and E > 200. The enzyme exhibited the highest enzyme activity among all reported (+)-γ-lactamases. The enzyme belongs to the isochorismatase-like hydrolases superfamily. The enzyme could be considered as the catalyst for the production of (-)-γ-lactam. Abstract: (-)-γ-Lactam ((-)-2-azabicyclo[2.2.1]hept-5-en-3-one) is a significant chiral synthon that can be used to synthesize a large number of carbocyclic nucleosides such as antiviral drugs abacavir and carbovir. As a new emerging group of enantioselective biocatalysts, (+)-γ-lactamase has drawn more and more attention because of its application for kinetic resolution of racemic γ-lactam to obtain optically pure (-)-γ-lactam. In this paper, a novel (+)-γ-lactamase (designated as SYJ322B5) derived from Bacillus thuringiensis was identified by genome mining method. The gene was cloned, functionally expressed in Escherichia coli system and the protein was purified to homogeneity. Subsequently, biochemical characterization of SYJ322B5 showed that the optimal temperature and pH were 50 °C and 7.0, respectively. Enzyme assay showed that the recombinant enzyme could enantioselectively catalyze the bioresolution of racemic γ-lactam with a high enantiomeric excess (ee) of 99.8% and enantiomeric ratio (E) >200. More importantly, SYJ322B5 exhibited the highest enzyme activity among all reported (+)-γ-lactamases. Bioinformatics analysis and molecular docking studies showed that the enzyme was not a conventional amidase superfamily member but belonged to the isochorismatase-like hydrolases superfamily. It possesses a conserved Asp9-Lys81-Cys114 catalytic triad like other members in which the cysteine is considered to perform nucleophilic attack in the enzymatic catalysis process. Overall, this novel (+)-γ-lactamase may become a potential tool for the production of (-)-γ-lactam.